Perancangan Aplikasi Berbasis Teknologi Internet Untuk Sistem Pengendali Alat Penyimpan Air - Mhd Zakki Fatahillah (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
The placement of water reservoirs at an altitude makes it difficult to know the condition of the water directly, so we need a system that can control and monitor in real time. In this study, a waterflow sensor has been used as a water flow reader, an ultrasonic sensor as a water level reader and a TDS sensor to detect water turbidity in a reservoir connected to an Arduino Atmega 2560. The Mamdani type fuzzy logic method is used to control the filling of water in a reservoir with level rules. water level and turbidity are controlled and monitored using IoT technology on smartphones. Based on the results of the study, it can be seen that the use of IoT in the control and monitoring system can facilitate monitoring the condition of reservoirs remotely in real time, where the data from the trial results obtained the highest success rate of the water filling process reaching 97% with an average error of less than 15%. So that this method can be applied to a smart home water reservoir control and monitoring system.